Writing in space, 1973-2019 - O'Grady, Lorraine 1934- (Duke University Press, 2020)
"WRITING IN SPACE is a collection of conceptual artist Lorraine O'Grady's writing, edited and introduced by Aruna D'Souza. The title comes from O'Grady's methodology of art creation, which began as text and moved into the visual art space throughout her career. O'Grady's career as a writer came before her art, but this book presents the work as a unified intellectual and artistic project. Her writing is deeply connected to her artwork, both speaking to each other. Complicated and thoughtful, O'Grady describes her work as "saying things that haven't been said before, so it takes a while before they can be heard." Divided into three parts, the book showcases a range of O'Grady's writing. The first brings together statements, scripts, and previously unpublished notes charting the development of her art. O'Grady has always insisted her images should be understood as a form of text- "writing in space"-thus her photo-collages will be reproduced as "visual essays" throughout the unfolding chronology. The second section gathers O'Grady's critical and theoretical essays on art and culture, setting the classic "Olympia's Maid" alongside essays on Jean-Michel Basquiat, Flannery O'Connor, William Kentridge, and others. The final section consists of interviews wherein O'Grady expands and complicates the intellectual terrain of her work, capturing the real-time movement of her thought and embodying her commitment to art as a profoundly discursive activity. In exploring black female subjectivity as an intimate and personal aspect of selfhood and as a function of larger cultural and historical forces, the goal of her work is not simply academic; it resonates, resisting essentialism. The transformative power of O'Grady's art and words allows the reader to sit with difference and allow tensions to coexist"--
Includes index
Keywords: O'Grady, Lorraine; O'Grady, Lorraine -- 1934-; Geschichte 1973-2019; Conceptual art; Words in art; Concept-art; USA; Aufsatzsammlung